"We need to work hand in hand": supporting cancer survivorship care with First Nations and Métis peoples in Canada via video. (March 2023) - Thomas, Roanne; Gifford, Wendy; Poudrier, Jennifer; Rheault, Alysson; Shallwani, Shirin
There is a lack of access to culturally safe and individualized cancer survivorship care and awareness of the unique challenges and strengths that Indigenous persons living with cancer (PLCs) face. This study aimed to explore the experiences and needs of First Nations and Métis PLCs across Canada. From 2014 to 2016, we engaged 87 participants who were either PLCs or caregivers (CGs) from five communities across Canada—Gitxsan and Kenora, British Columbia; Ottawa, Ontario; and Akwesasne and Kahnawake, Quebec—using participatory arts-based methods. Following the thematic analysis of participants' photographs, journal entries, and stories, we created a video exploring the themes of spirituality and ceremony, finding strength together, the land and nature, creating and sharing, and navigating health care. Participants' feedback on the video supports the use of video as a knowledge translation tool that may promote meaningful dialogue around the cancer experiences of Indigenous peoples in Canada.